Parenthood and childhood in face of challenges of modernity – (not)obvious reflections - Ornacka, Katarzyna (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The sphere of family life and the processes occurring within it are a constant source of inspiration for researchers, politicians and reformers of social life. This sphere is also the subject of interest of many scientific disciplines and the area within which the public discourse develops. Moreover, the sphere of family life encompasses various theoretical and research perspectives, thanks to which it leaves space for reflection on constantly emerging issues or phenomena that significantly affect the functioning of individuals and family systems. Researchers agree that the contemporary family is in an extremely difficult situation, connected with the pace of changes. It faces the necessity of working out adaptation mechanisms that will enable the optimal development of all its members. This concerns two issues: working out a new space for family functioning, which includes „old” and new patterns of behavior or building mutual relations, and combining self-reflection with work on raising children. In this richness of family life, it is worth reflecting on what constitutes the foundation of family practice – the home and the nature of the (non-)presence of its individual members. The aim of this paper will therefore be to reflect on the phenomenon of parenthood and childhood in the space of their (non-)presence and the ways in which they are manifested in the context of the coronavirus pandemic.